See what we eat! : a first book of healthy eating - Ritchie, Scot (Ritchie, Scot. Exploring our community., 2017)
"The book opens with Nick, Yulee, Pedro, Sally and Martin -- the five friends from Follow That Map! (2009), Look at That Building! (2011) and Look Where We Live! (2015) - about set off for Yulee's Aunt Sara's farm for some apple-picking. Their plan is to pick some apples to use in a dessert they will take to their neighborhood's potluck celebrating the fall harvest. While on their agricultural adventure, they discover how food is grown and produced before it ends up in their kitchens and on their plates. Each stop on their tour of the farm introduces a basic food group: a field of wheat and oats for the grains, the colourful veggie garden for vegetables, the henhouse for protein, the barn for dairy and its alternatives, and finally the orchard for fruit. After having some fun picking apples and then taking a break to eat a nutritious snack, it's time to go home to make an apple crisp. On the way, the kids spot a food terminal and stop in at a grocery store for some missing ingredients. Then with the help of Pedro's dad, all the kids play a role in making the crisp, including taking the food scraps out to the compost. Once the crisp is ready, the friends take it to the community center, where a multicultural group of neighbours has gathered to share homemade foods and celebrate the bounty of the season. Endmatter includes a simple baking activity (apple crisp recipe) and a glossary."--